An Improved Weighted Clustering for Ad-hoc Network Security New - Verma, Basant Kuamr; Kumar, Binod (International Journal of Computer Sciences and Engineering, 2015)
Wireless network technology is most frequently used network technology. A number of variants are available on the basis of traditional wireless networking such as WSN, WMN, MANET and others. In all the variants of wireless networks routing plays the essential role. Additionally the attackers are mainly targeting the routing strategies for performing the malicious activities. In order to secure the wireless ad hoc network a new kind of security system is proposed in this presented paper. The proposed security architecture provides the security against the malicious attackers namely black-hole, wormhole, grey-hole and DDOS attacks. Additionally able to improve the performance of network in normal conditions as well as under attack conditions. The given paper includes the proposed system design and the concepts that are help to support the proposed security infrastructure